After the Fall of the Caravan Kingdoms. Notes about the Occupation of Sumhuram and the Area of Khor Rori (Oman) from the Fifth Century AD to the Islamic Period - Pavan, Alexia (Études et Travaux, 2024)
Since the beginning of the investigations in the area of Khor Rori and at the site of Sumhuram, the easternmost outpost of the caravan kingdoms along the southern coast of the Arabian Peninsula, cultural material and architectural evidence seemed to exclude frequentation, both permanent and seasonal, during the Islamic period. Indeed, it was assumed that any form of occupation, which had begun in the second century BC, ceased in the fifth century AD, consistent with the historical, economic and cultural scenario that marked the end of the caravan kingdoms. However, discoveries made during more recent fieldwork, along with a critical reinterpretation of previously collected data, have clearly demonstrated the existence of a late occupation of the area, which can be tentatively dated to the Late Antique period in the case of the burials located nearby and to the Islamic period in the case of the reoccupation of the site. This paper will discuss the preliminary results of the re-analysis of the late evidence, focusing on the last architectural structures, the small finds and some of the pottery.